Prolonged persistence of mutagenic DNA lesions in somatic cells - Michael Spencer Chapman; Emily Mitchell; Kenichi Yoshida; Nicholas Williams; Margarete A. Fabre; Anna Maria Ranzoni; Philip S. Robinson; Lori D. Kregar; Matthias Wilk; Steffen Boettcher; Krishnaa Mahbubani; Kourosh Saeb Parsy; et al. (Nature, 2025)
Abstract DNA is subject to continual damage, leaving each cell with thousands of individual DNA lesions at any given moment 1–3 . The efficiency of DNA repair means that most known classes of lesion have a half-life of minutes to hours 3,4 , but the extent to which DNA damage can persist for longer durations remains unknown. Here, using high-resolution phylogenetic trees from 89 donors, we identified mutations arising from 818 DNA lesions that persisted across multiple cell cycles in normal human stem cells from blood, liver and bronchial epithelium 5–12 . Persistent DNA lesions occurred at increased rates, with distinctive mutational signatures, in donors exposed to tobacco or chemotherapy, suggesting that they can arise from exogenous mutagens. In haematopoietic stem cells, persistent DNA lesions, probably from endogenous sources, generated the characteristic mutational signature SBS19 13 ; occurred steadily throughout life, including in utero; and endured for 2.2 years on average, with 15–25% of lesions lasting at least 3 years. We estimate that on average, a haematopoietic stem cell has approximately eight such lesions at any moment in time, half of which will generate a mutation with each cell cycle. Overall, 16% of mutations in blood cells are attributable to SBS19, and similar proportions of driver mutations in blood cancers exhibit this signature. These data indicate the existence of a family of DNA lesions that arise from endogenous and exogenous mutagens, are present in low numbers per genome, persist for months to years, and can generate a substantial fraction of the mutation burden of somatic cells.